Synthesis, structural characterization, reactivity and catalytic activity of mixed halo/triflate ArI(OTf)(X) species. Issue 11 (21st February 2023) - Sharp-Bucknall, Lachlan; Sceney, Marcus; White, Keith F.; Dutton, Jason L.
Abstract : Targeted isolation of two previously inaccessible I(iii ) halotriflates. The chloride analoge is a powerful electrophilic chlorinating reagent that can be generated in a catalytic manner to enhance Cl2 reactivity. Abstract : Both mixed λ 3 -iodoarenes and λ 3 -iodoarenes possessing –OTf ligands are coveted for their enhanced reactivities. Here we describe the synthesis, reactivity, and comprehensive characterisation of two new ArI(OTf)(X) species, a class of compound that were previously only invoked as reactive intermediates where X = Cl, F and their divergent reactivity with aryl substrates. A new catalytic system for electrophilic chlorination of deactivated arenes using Cl2 as the chlorine source and ArI/HOTf as the catalyst is also described.